Low incentives to work at the extensive and intensive margin in selected EU countries - H. Xavier Jara; Katrin Gasior; Mattia Makovec (University of Essex, Institute for Social and Economic Research (ISER), 2017)
Tax and benefit systems play an important role in determining work incentives at both, the extensive and the intensive margin of labour supply. The aim of this research note is to provide a comparative analysis of work incentives in selected EU countries. Our analysis makes use of EUROMOD and representative household microdata from nine EU countries (Belgium, Bulgaria, Germany, Italy, Lithuania, Hungary, Austria, Finland and the UK) to provide a description of the distribution of short- and long-term participation tax rates and marginal effective tax rates in 2015, for people currently in work; and to characterise individuals facing low work incentives. Our results highlight the important variation in the distribution of work incentives across our selected countries. Unemployment insurance schemes play a significant role in short-term participation tax rates, although to different extents across countries. Our analysis further highlights differences across countries in terms of the population subgroups with low incentives to work and discusses the relevance of using a relative or an absolute threshold for such definition.
Keywords: H31; E60; 330; work incentives; extensive margin; intensive margin